Neuroticism Trait Personality, Resilience, and Loneliness in Adolescent Victims of Bullying - Veronica Tiffani Nugroho; Arthur Huwae (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Adolescent victims of bullying often experience significant psychological distress, including stigma, social withdrawal, and emotional instability. This study examines the predictive roles of neuroticism trait personality and resilience on loneliness in adolescents who have experienced bullying. Addressing a gap in the literature—particularly within the Indonesian adolescent context—this research uniquely explores the combined influence of a vulnerability factor (neuroticism) and a protective factor (resilience) in relation to loneliness, a critical mental health concern. A quantitative approach was employed using a multiple linear regression design. Participants included 232 adolescents aged 12–21 who had experienced bullying, selected through incidental sampling. The instruments used were the Big Five Inventory (Neuroticism subscale), the Brief Resilience Scale (BRS), and the De Jong Gierveld Loneliness Scale (DJGLS). The results showed that both neuroticism and resilience significantly predicted loneliness (F = 44.75, p < .001, R² = .281). Specifically, neuroticism positively predicted loneliness, while resilience negatively predicted it. These findings contribute to a deeper understanding of how personality traits and coping resources interact in shaping adolescents' psychological responses to bullying. The study’s novelty lies in its simultaneous investigation of neuroticism and resilience within a culturally specific bullying context. The results offer practical implications for designing preventive and therapeutic interventions aimed at reducing loneliness and promoting emotional well-being among adolescent victims of bullying.